**log**(5x)-

_{3}**log**(6)=2

_{3}-
CREATE FREE ACCOUNT
- Access thousands of free resources from expert tutors
- Comment on posts and interact with the authors
- Ask questions and get free answers from tutors
- View videos, take interactive quizzes, and more!

- Become a Student
- Become a Student
- Sign In

Tutors, please sign in to answer this question.

The base on the logarithm tells you what base you need when reversing the operation algebraically.

first combine the two logs

log_{3}(5x/6)=2

Then use base three to get rid of the logarithm

3^log_{3}(5x/6)=3^2

5x/6=9

5x=54

x=10.8

you can check this on your calculator by the change of base formula

log_{3}(5x)=ln(5x)/ln(3)

Lohith D.

Test Prep, Science, Math, and Writing Tutor

Roselle Park, NJ

4.8
(26 ratings)

Sunil S.

Sciences and test prep

Staten Island, NY

4.5
(10 ratings)

Austin M.

Algebra I, Algebra II, Pre-Algebra

Union, NJ